Faktor Gizi yang Mempengaruhi Stunting Pada Balita: Nutritional Factors Affecting Stunting Among Toddlers - Nindi Kusuma Dewi; Herdhika Ayu Retno Kusumasari; Sri Andarini; I Wayan Agung Indrawan (Universitas Airlangga, 2023)
Background: Stunting is one of Indonesia's most serious nutritional issues. Malang Regency has a 12 percent prevalence of stunting in 2020, with Gondanglegi sub-district having 942 stunted children. One effort to improve toddler nutrition is the administration of colostrum, exclusive breastfeeding, and complementary feeding. Inappropriate colostrum administration, exclusive breastfeeding, and complementary feeding can all increase the risk of stunting in toddlers. Aims: this study aimed to identify the factors that cause stunting in toddlers based on their behavior in meeting their nutritional needs in Gondanglegi sub-district, Malang Regency. Methods: A total of 136 children aged 6 to 59 months were divided into two equal groups for the case-control study. The research was carried out at Ketawang and Gondanglegi Primary Health Centers in Indonesia's Gondanglegi sub-district. Weight and height measurements, a questionnaire-based interview, and a 24-hour food recall were all collected. With a significance level of 0,05, Chi-square was used to determine the factors influencing stunting. To perform multivariate analysis, logistic regression was used. Results: Colostrum administration, exclusive breastfeeding, and complementary feeding were all linked to stunting in bivariate analysis (p< 0.05). According to a multivariate analysis, exclusive breastfeeding (OR=4,8) is strongly associated with stunting among toddlers in Gondanglegi sub-district, Malang Regency, Indonesia. Conclusion: Breast milk contains many nutrients and antibodies that can protect babies from infection by reducing the duration and severity of illness that can lead to chronic malnutrition and stunting.